Device for automated screening of irradiation wavelength and intensity – investigation of the wavelength dependence of photoreactions with an arylazo sulfone in continuous flow. Issue 9 (17th June 2022) - Roider, Thomas; Frommknecht, Norbert; Höltzel, Alexandra; Tallarek, Ulrich
Abstract : A system allowing the automatic change of LED arrays (normalized to the number of emitted photons) is presented to study photochemical reactions in continuous flow for their wavelength dependence. Abstract : We introduce a device that allows programmable, automated changes of the irradiation wavelength and intensity for use with a continuous-flow photoreactor. Combined with parallel chromatographic analysis, the set-up enables systematic screening of photoreactions in a remarkably short time frame. This is demonstrated by investigating the photoconversion of an arylazo sulfone under different reaction conditions, with and without the use of an additive. Data obtained from a series of systematic wavelength screenings at defined irradiation intensity reveal a previously unknown intermediate and disclose a new, wavelength-dependent reaction pathway. Our study shows how systematic screening of the wavelength and irradiation intensity can contribute to the fundamental understanding of photochemical reactions.